Association of Residual Feed Intake with Performance Traits in Two Different Crossbred Chicken - Vasupvani, Bhonagiri; Dubey, P. P.; Sahoo, S. K.; Uniyal, Sandeep; Grewal, R. S. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during February, 2024 to January, 2025 at the Poultry Research Farm of the Directorate of Livestock Farms, Guru Angad Dev Veterinary and Animal Sciences, University, Ludhiana to study the residual feed intakes (RFI) and their association with performance traits in two distinct chicken crosses viz Desi cross 1 (Rhode Island Red x Punjab Brown) and Desi cross 2 (Punjab Red×Punjab Brown). RFI was calculated at three phases: one at the grower phase, 16–20 weeks (RFI 1), and two at the layer phase, 28–33 weeks (RFI 2), and 36–40 weeks (RFI 3). Statistical analysis revealed significant differences in performance traits in between the crosses. The association between RFIs and performance traits in Desi cross 1 here also RFI 1 and RFI 2 are not affected by any performance traits. Remarkably, RFI 3 in Desi cross 1 showed a negative correlation with late-stage body weight and egg weight, while RFI in Desi cross 2 depicted positive correlations with egg production traits. Additionally, partial regression analysis identified egg mass as a significant factor influencing expected feed intake in Desi cross 2. The predicted partial regression coefficient for RFI may be useful for the selection of these two Different Crossbred Chicken to improve their feed efficiency. These findings highlight the importance of considering RFI as a selection tool in poultry breeding program for reduction in feed requirement without compromising the performance traits in chicken.